PENGARUH JUMLAH KUNJUNGAN WISATAWAN, TINGKAT HUNIAN KAMAR, JUMLAH RESTORAN TERHADAP PAJAK HOTEL & RESTORAN DAN PDRB KAWASAN REGIONAL SARBAGITA DI PROVINSI BALI - Pertiwi, Ni Luh Gde Ana; Sri Budhi, I Made Kembar; Nyoman Saskara, Ida Ayu (Buletin Studi Ekonomi; VOL.22.NO.1. FEBRUARI 2017 (PP 1-112)DO - 10.24843/bse.2017.v22.i01.p02, 2017)
The result of this research showed that the Total of Tourists Visit, Room Occupancy Rate, Amount of Restaurants positive and significantly influenced to the Hotel and Restaurant Tax. Total of Tourists Visit, Room Occupancy Rate, Amount of Restaurants positive and significantly influenced to the GDRP, Hotel and Restaurant negative and significantly influenced to the GDRP. Tax Hotel and Restaurant Tax is not a variabel, which mediate the influenced of Total of Tourists Visit, Room Occupancy Rate, Amount of Restaurants to the GDRP. Based on the conclusions, the suggestions is to the government have to maintain the quality of tourism facilities, especially hotels and restaurants as well and create an equitable development in the tourism.